(untitled) - Oliver, Chris (Chicago, 2010)
Practical advice for catalogers and library administrators on how to make the transition from the Anglo-American cataloging rules (AACR) to Resource description and access (RDA).
Keywords: Cataloging,Descriptive cataloging; Standards,Standards